Research Progress in Surface Modification of Carbon Nanotubes - Chen, Cheng; Wang, Siyu; Zhong, Rui; Fan, Zexi; Qian, Penghua (Scientific Journal of Technology, 2026)
Carbon nanotubes (CNTs) are a kind of nanomaterial with a unique one-dimensional hollow structure and excellent mechanical and electrical properties. Because of their excellent mechanical strength, high aspect ratio, and good electrical and thermal conductivity, CNTs have been applied in many fields. In addition, its unique nanotube structure and large specific surface area are conducive to the construction of stable carrier transport channels, making it a hot spot in the field of polymer composites. However, CNTs are chemically inert on the surface, and strong van der Waals interactions exist between the tubes, which easily form aggregates, seriously restricting their dispersion in the matrix and interface bonding ability. Surface modification of CNTs has become a key way to overcome their limitations and enhance their potential. Functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on CNTs can form covalent bonds or hydrogen bonds with polar groups in the polymer matrix to promote load transfer efficiency. The interaction between the nanofiller and polymer can also improve the mechanical properties of composites. Therefore, the preparation, modification, and application of CNTs in polymer composites are reviewed in this paper, and the challenges and potential future research directions in the field of composites are evaluated.